Consequences of culture and diversity for governmental redistribution - Klaus Gründler; Sebastian Köllner (Julius Maximilian University of Würzburg, Chair of Economic Order and Social Policy, 2017)
We empirically study the effects of culture and diversity on government redistribution based on a large sample of countries. To disentangle culture from institutions, our analysis employs regional instruments as well as data on the prevalence of the pathogen Toxoplasma Gondii, linguistic differences, and the frequency of blood types. Redistribution is higher in countries with (1) loose family ties and individualistic attitudes, (2) high prevalence of trust and tolerance, (3) low acceptance of unequally distributed power and obedience, and (4) a prevalent belief that success is the result of luck and connections. Apart from their direct effects, these traits also exert indirect impact by influencing the transmission of inequality to redistribution. Finally, we show that redistribution and diversity in terms of culture, ethnic groups, and religion stand in a non-linear relationship, where moderate levels of diversity impede redistribution and higher levels offset the generally negative effect.
Keywords: I38; Z1; D72; D31; 330; Culture; Redistribution; Diversity